Crustal‐scale seismic profiles across the Manila subduction zone: The transition from intraoceanic subduction to incipient collision. Issue 1 (7th January 2014) - Eakin, Daniel H.; McIntosh, Kirk D.; Van Avendonk, H. J. A.; Lavier, Luc; Lester, Ryan; Liu, Char‐Shine; Lee, Chao‐Shing
Abstract [1] We use offshore multichannel seismic (MCS) reflection and wide‐angle seismic data sets to model the velocity structure of the incipient arc‐continent collision along two trench perpendicular transects in the Bashi Strait between Taiwan and Luzon. This area represents a transition from a tectonic regime dominated by subduction of oceanic crust of the South China Sea, west of the Philippines, to one dominated by subduction and eventual collision of rifted Chinese continental crust with the Luzon volcanic arc culminating in the Taiwan orogeny. The new seismic velocity models show evidence for extended to hyperextended continental crust, ~10–15 km thick, subducting along the Manila trench at 20.5°N along transect T1, as well as evidence indicating that this thinned continental crust is being structurally underplated to the accretionary prism at 21.5°N along transect T2, but not along T1 to the south. Coincident MCS reflection imaging shows highly stretched and faulted crust west of the trench along both transects and what appears to be a midcrustal detachment along transect T2, a potential zone of weakness that may be exploited by accretionary processes during subduction. An additional seismic reflection transect south of T1 shows subduction of normal ocean crust at the Manila trench.